Використання в культурі та сучасний стан інтродукції східноазійських видів роду Berberis L. в умовах Правобережного Лісостепу України - Yakobchouk, О.М.; Parkhomenko, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The history of use in the culture of barberry are elucidated. The results of introduction trials in the right-bank of forest-steppe of Ukraine of eastasian species of the genus Berberis L. are given.